Basá busá: riqueza, cultura e política no alto rio Negro - Ferreira, Tatiana Amaral Sanches (2014)
This work presents ethnographic research concerning recent initiatives of cultural revitalization in the Alto Rio Negro region, particularly those initiatives that have been taken by tukano speaking groups in the Uaupés river basin. Therefore, this study is a combination of short-term field work and bibliographic research. The case under analysis is that of the recent repatriation of a set of ceremonial ornaments (basá basá), which had been kept for decades at the Museu do Índio in the city of Manaus. Considering the impossibility of defining the communities to which these pieces had originally belonged, it was decided that the repatriated ornaments would become the collective property of the indigenous peoples of the Uaupés river basin, in custody of an indigenous organization pertaining to the multiethnic group of Iauaretê. This research showed that the ornaments are considered to be people with agency, in such a way that concerns relating to the appropriate uses and circulation of these objects arouse anxiety as to the misfortunes that such objects could bring about to those who used or manipulated them. However, some people from Iauarete affirmed that the ornaments could not only be tamed and revitalized, but also transmit important knowledge to those who used them.